Massive tree mortality from flood pulse disturbances in Amazonian floodplain forests: The collateral effects of hydropower production - Resende, Angélica Faria de (2019)
Large dams built for hydroelectric power generation alter the hydrology of rivers, attenuating the flood pulse downstream of the dam and impacting riparian and floodplain ecosystems. The present work mapped black-water floodplain forests (igapó) downstream of the Balbina Reservoir, which was created between 1983 and 1987 by damming the Uatumã River in the Central Amazon basin. We apply remote sensing methods to detect tree mortality resulting from hydrological changes, based on analysis of 56 ALOS/PALSAR synthetic aperture radar images acquired at different flood levels between 2006 and 2011. Our application of object-based image analysis (OBIA) methods and the random forests supervised classification algorithm yielded an overall accuracy of 87.2%. A total of 9800 km 2 of igapó forests were mapped along the entire river downstream of the dam, but forest mortality was only observed below the first 49 km downstream, after the Morena rapids, along an 80-km river stretch. In total, 12% of the floodplain forest died within this stretch. We also detected that 29% of the remaining living igapó forest may be presently undergoing mortality. Furthermore, this large loss does not include the entirety of lost igapó forests downstream of the dam; areas which are now above current maximum flooding heights are no longer floodable and do not show on our mapping but will likely transition over time to upland forest species composition and dynamics, also characteristic of igapó loss. Our results show that floodplain forests are extremely sensitive to long-term downstream hydrological changes and disturbances resulting from the disruption of the natural flood pulse. Brazilian hydropower regulations should require that Amazon dam operations ensure the simulation of the natural flood-pulse, despite losses in energy production, to preserve the integrity of floodplain forest ecosystems and to mitigate impacts for the riverine populations.